2016
DOI: 10.1161/circulationaha.115.017001
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Inpatient and Observation Rehospitalizations After Acute Myocardial Infarction

Abstract: Background— Previous studies examining early readmission after acute myocardial infarction have focused exclusively on inpatient readmissions. However, from a patient’s perspective, any unplanned inpatient or observation rehospitalization after acute myocardial infarction represents a significant event; these unplanned rehospitalizations have not been well characterized. Methods and Results— We examined all patients with acute myocardial infarction trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This increased readmission risk does not only apply to patients with formal mental illness diagnoses. Self-reported depressive symptoms and low quality of life ratings, have been found to be the patient-level characteristics, most strongly associated with readmission following AMI (14). …”
Section: Introductionmentioning
confidence: 99%
“…This increased readmission risk does not only apply to patients with formal mental illness diagnoses. Self-reported depressive symptoms and low quality of life ratings, have been found to be the patient-level characteristics, most strongly associated with readmission following AMI (14). …”
Section: Introductionmentioning
confidence: 99%
“…Accurate risk stratification and diagnostic testing are critical for time dependent therapies that restore blood flow to the compromised myocardium, thereby reducing morbidity and mortality and avoiding inappropriate hospital discharge (Hess et al, ; Pelter, ). To minimize total ischemic burden time, the American Heart Association and European Society of Cardiology (AHA/ESC) recommend that individuals with chest pain seek medical attention immediately and receive a 12‐lead electrocardiogram (ECG) within 10 min of hospital arrival, based on evidence that longer delays are associated with adverse prognoses (O'Gara et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with white pa- tients and men, black patients and women were less likely to be employed and reported greater financial burden of medications, potentially resulting in greater overall financial stress and, more specifically, reduced access to health care, evidence-based post-MI treatments, and antianginal medications. Black and female patients also reported lower quality of life, which is another factor associated with worse post-MI outcomes 17 ; this may reflect not only financial difficulties and worse physical condition, but also perhaps other stressors, such as the role of primary caregiver in a family and poor mental well-being. In addition, a prior study examining race and 30-day readmissions after MI, pneumonia, and heart failure among Medicare beneficiaries found that disparities in readmission rates were related not only to race, but also to hospital site.…”
Section: Discussionmentioning
confidence: 99%
“…As previously defined, 17 rehospitalizations were any hospital visits involving at least 1 overnight stay and included inpatient readmission or observation stays as classified by hospital billing data. Hospital visits without an overnight stay and rehabilitation visits were not considered rehospitalizations.…”
Section: Clinical Perspectivementioning
confidence: 99%